1998
DOI: 10.1002/(sici)1521-4141(199808)28:08<2549::aid-immu2549>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of self-reactive B cells by provision of T cell helpin vivo

Abstract: We have previously demonstrated that antigen-specific T cell help can rescue mature Ig transgenic (Tg) hen egg lysozyme (HEL)-specific B cells from tolerance induction upon transfer into soluble HEL-expressing Tg hosts. Here we extend these findings by showing that T cell help could also rescue both immature and mature self-reactive B cells from rapid deletion in response to high-avidity membrane-bound HEL. Moreover, although short-lived anergic peripheral B cells that had matured in the presence of soluble se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 37 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…One point to be kept in mind when interpreting studies on the role of T-cell help in reversing B-cell anergy is the availability of T-cell help relative to the timing of self-antigen-induced signalling. Cook et al 50 have shown that T-cell-derived signalling must be available soon after self-antigen-induced signals are delivered to the B cells to prevent the induction of anergy.…”
Section: Decreased Lifespanmentioning
confidence: 99%
“…One point to be kept in mind when interpreting studies on the role of T-cell help in reversing B-cell anergy is the availability of T-cell help relative to the timing of self-antigen-induced signalling. Cook et al 50 have shown that T-cell-derived signalling must be available soon after self-antigen-induced signals are delivered to the B cells to prevent the induction of anergy.…”
Section: Decreased Lifespanmentioning
confidence: 99%
“…DCs have been shown to both positively and negatively regulate autoantibody production [5][6][7]. Helper T cells, or signals associated with T-cell help, appear to negatively regulate B-cell tolerance [8][9][10][11][12]. It remains unclear as to which helper T-cell populations can support autoantibody production.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, such cells may be rescued, activated, and expanded if provided with Th cell help (13), a feature that also was found for anergic B cell responses of other autospecificities (14,15). However, in contrast to B cells, it is unclear what specificity Th cells may have in cognate interactions with dsDNA-specific B cells.…”
mentioning
confidence: 98%